2015
DOI: 10.1111/1471-0307.12257
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of the kappa‐casein and beta‐lactoglobulin genes in Anatolian water buffalo by PCRRFLP

Abstract: The objective of this study was to identify allele and genotype frequencies of the j-CN and b-LG genes in Anatolian water buffalo. A total of 126 water buffalos from Turkey were genotyped using the PCR-RFLP method. For gene j-CN, only B allele and BB genotype were observed. And for gene b-LG, two types of alleles (A and B) and three types of genotypes were observed. The genotype frequencies of AA, AB and BB of b-LG in Anatolian water buffalo were 0.254, 0.698 and 0.048, respectively. Surprisingly, the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Those fragments are termed as allels. This finding is different from cattle which has polymorphic for the kappa casein gene (Doosti et al 2011;Khaizaran & Al-Razem 2014;Cinar et al 2016). This finding of genotype BB in all buffalo samples (swamp and river) in Indonesia is similar to previous reports of allel frequencies which found in most of buffalo (Table 2).…”
Section: Genotyping Of Kcn Genesupporting
confidence: 78%
“…Those fragments are termed as allels. This finding is different from cattle which has polymorphic for the kappa casein gene (Doosti et al 2011;Khaizaran & Al-Razem 2014;Cinar et al 2016). This finding of genotype BB in all buffalo samples (swamp and river) in Indonesia is similar to previous reports of allel frequencies which found in most of buffalo (Table 2).…”
Section: Genotyping Of Kcn Genesupporting
confidence: 78%
“…PCR-RFLP results using AcuI enzyme disagreed with the majority of reviewed PCR-RFLP studies conducted by HindIII , HinfI or MaeII restriction enzymes which concluded that, all Egyptian buffaloes were monomorphic and genotyped as homozygous "BB" animals as reported by Othman (2005); El-Rafey and Darwish (2008); and Abdel Dayem et al (2009). Similar results were also noticed, in Pakistani buffalo (Riaz et al, 2008;Ghafoor et al, 2015), in Indian buffalo (Gangaraj et al, 2008;Shende et al, 2009;Nair et al, 2011;George et al, 2018), in Brazilian buffalo (Otaviano et al, 2005), in Chinese water buffalo (Ren et al, 2011) , in Iraqi buffalo (Jaayid et al, 2013), in Anatolian water buffalo breed (Cinar et al, 2016), in swamp and river Indonesian buffaloes (Margawati et al, 2016), in Cuban buffalo (Marrero et al, 2016), and in Iranian buffalo (Abbasi et al, 2009).…”
Section: Detection Of Polymorphism and Genetic Variants Of κ-Cn And β-Lgsupporting
confidence: 65%
“…Also, the dominance of "BB" genotype (0.66) was reported by Karimi et al (2009). On contrary, Patel et al (2007) and Cinar et al (2016) noticed the predominance of heterozygous "AB" with genotypic frequencies of 0.586 and 0.698, respectively.…”
Section: Allelic and Genotypic Frequencies Of Studied Genesmentioning
confidence: 92%
See 1 more Smart Citation
“…A polymorphism in Pit1 gene was associated with milk traits in Egyptian and Indian buffaloes (Othman et al, 2011;Parikh and Rank, 2013). In addition, water buffaloes carry polymorphism in the KCN gene (Cinar et al, 2015;Mitra et al, 1998), which can affect their milk yield as well as feta cheese processing parameters (Shakerian et al, 2016).…”
Section: Discussionmentioning
confidence: 99%